Tooth extractions in Orthodontics: first or second premolars? - Araújo,Telma Martins de (2019)
ABSTRACT Tooth crowding and protrusions demand rigorous attention during orthodontic planning that includes the extraction of first and second premolars. Some characteristics, such as dentoalveolar bone discrepancies, maxillomandibular relations, facial profile, skeletal maturation, dental asymmetries and patient cooperation, are important elements of an orthodontic diagnosis. This study discusses the options of treatments with extractions and describes the correction of a Class I malocclusion, bimaxillary protrusion, severe anterior crowding in both dental arches and tooth-size discrepancy, using first premolar extractions.